Functioning of Innovative Territorial Clusters - Gureva, Maria A.; Lyubimtseva, Svetlana V.; Tukhkanen, Tatiana N.; Lyubimtseva, Olga Yu.; Simonova, Lyudmila M.; Kolpak, Eugeny P. (International Journal of Economics and Financial Issues, 2016)
One of the basic directions of development of modern economy, closely related, primarily, to the innovative nature of this development is in the process of forming clusters. Regional and interregional clusters are considered as a priority inter-sectoral complexes that determine the development of post-industrial information economy at the national and regional level. Their development is associated with the processes of globalization and formation of the industrial structure of the information economy. The tasks of Russia’s transition to innovative type of development are associated in particular with the need of formation of innovative clusters. Clusters as a form of spatial associations of enterprises is widespread in the Western economies. Taking into account the necessity of innovative development of Russia in the context of improving the competitiveness of industries and sectors in terms of integration of the country into the global economy, we consider it appropriate in this work to conduct a study of foreign experience of formation of clusters (Cherenkov, 2013). From the definition given by the founder of the modern theory of clusters by M. porter, that “...a cluster or industrial group, is a group of geographically neighboring interconnected companies and related organizations operating in a certain area, characterized by common activities and complementary to each other”. Keywords: cluster, territorial-production cluster, globalization, innovation JEL Classifications: P25, P28, R1, R12